The Lifelong Learning of Mother Teachers Learners - Pément, Nancy-Jean (Allies for Education, 2018)
In another life, Dr. Nancy-Jean Pément was a researcher and strategic planner with the Ministry of the Solicitor General and at the Department of Justice Canada. Her research on victim policy and legislation informed amendments to the Criminal Code, as well as programs and policies relating to the National Family Violence Initiative and the National Crime Prevention Council among others. She has taught in the Faculty of Social Sciences at the University of Ottawa—the world’s largest bilingual French-English university—and at the Collège d’enseignement général et professionnel in Québec. In California, she worked at CSU Northridge on its reaccreditation and for the Vice-Provost. Currently, she teaches in the Masters of Higher Education Leadership program at CSUCI. Her research interests include the sociology of higher education, women’s lives in the academy, doctoral study, the sociology of law, victimization and peacemaking. Nancy enjoys poetry and has been published in literary magazines in the US and Canada. She is Jackson’s mom.